Putting Reasons in their Place - Gascón, José Ángel (Informal Logic)

(untitled) (Informal Logic, 2020)
Hilary Kornblith has criticised reasons-based approaches to epistemic justification on the basis of psychological research that shows that reflection is unreliable. Human beings, it seems, are not very good at identifying our own cognitive processes and the causes of our beliefs. In this article I defend a conception of reasons that takes those empirical findings into account and can avoid Kornblith’s objections. Reasons, according to this account, are not to be identified with the causes of our beliefs and are useful first and foremost in argumentation instead of reflection.